The transcriptional regulator Lrp activates the expression of genes involved in the biosynthesis of tilimycin and tilivalline enterotoxins in Klebsiella oxytoca - Miguel A. De la Cruz; Hilda A. Valdez-Salazar; Diana Rodríguez-Valverde; Santa Mejia-Ventura; Nayely Robles-Leyva; Tania Siqueiros-Cendón; Quintín Rascón-Cruz; Nancy León-Montes; Jorge Soria-Bustos; Fernando Chimal-Cázares; Roberto Rosales-Reyes; María L. Cedillo; et al. (mSphere)
ABSTRACT The toxigenic Klebsiella oxytoca strains secrete tilymicin and tilivalline enterotoxins, which cause antibiotic-associated hemorrhagic colitis. Both enterotoxins are non-ribosomal peptides synthesized by enzymes encoded in two divergent operons clustered in a pathogenicity island. The transcriptional regulator Lrp (leucine-responsive regulatory protein) controls the expression of several bacterial genes involved in virulence. In this work, we have uncovered novel findings that have significant implications. We determined the transcriptional expression of aroX and npsA, the first genes of each tilimycin (TM)/tilivalline (TV) biosynthetic operon in K. oxytoca MIT 09-7231 wild-type and its derivatives Δlrp mutant and complemented strains. Our results suggest that Lrp directly activates the transcription of both aroX and npsA genes by binding to the intergenic regulatory region in a leucine-dependent manner. Furthermore, the lack of Lrp significantly diminished the cytotoxicity of K. oxytoca on HeLa cells due to reduced production of TM and TV. Altogether, our data present a new perspective on the role of Lrp as a regulator in cytotoxin-producing K. oxytoca strains and how it controls the expression of genes involved in the biosynthesis of their main virulence factors.IMPORTANCETilimycin (TM) and tilivalline (TV) are enterotoxins that are a hallmark for the cytotoxin-producing Klebsiella oxytoca strains, which cause antibiotic-associated hemorrhagic colitis. The biosynthesis of TM and TV is driven by enzymes encoded by the aroX- and NRPS-operons. In this study, we discovered that the transcriptional regulator Lrp plays a crucial role in activating the expression of the aroX- and NRPS-operons, thereby initiating TM and TV biosynthesis. Our results underscore a molecular mechanism by which TM and TV production by toxigenic K. oxytoca strains is regulated and shed further light on developing strategies to prevent the intestinal illness caused by this enteric pathogen.